2007
DOI: 10.1111/j.1751-1097.2007.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Interaction of Hypericin in Low‐density Lipoprotein— A Photophysical Study

Abstract: The accumulation and interaction of hypericin with the biologically important macromolecule, low-density lipoprotein (LDL), is investigated using various steady-state and time-resolved fluorescence measurements. It is concluded that multiple hypericins can penetrate considerably deeply into the LDL molecule. Up to approximately 20 nonaggregated hypericin molecules can enter LDL; but upon increasing the hypericin concentration, the fluorescence lifetime of hypericin decreases drastically, suggesting most likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…In addition, starting at ca Hyp/LDL = 60:1 ratio, Hyp fluorescence kinetics exhibit more complex behavior with two fluorescence lifetimes. As it was previously suggested, the multiple decay components may indicate that the various fractions of Hyp molecules are differently self‐quenched in different parts of LDL particle (21,22,37,38).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, starting at ca Hyp/LDL = 60:1 ratio, Hyp fluorescence kinetics exhibit more complex behavior with two fluorescence lifetimes. As it was previously suggested, the multiple decay components may indicate that the various fractions of Hyp molecules are differently self‐quenched in different parts of LDL particle (21,22,37,38).…”
Section: Resultsmentioning
confidence: 89%
“…2. The observed fluorescence is due to Hyp monomeric form incorporated in LDL particles (19–22). It is evident that there are at least two phases of the Hyp incorporation into LDL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggested that the lipoprotein might serve as a vehicle only during hypericin transport, and that hypericin was released from the lipoprotein complex before reaching the necrotic tumor tissue 12, 60. Several reports have confirmed that the LDL and LDL receptor pathway plays an important role in the delivery of hypericin into the cells 61-63.…”
Section: The Mechanism Of Necrosis Avidity Behind Hypericinmentioning
confidence: 76%
“…In the presence of the plasma (lipo)proteins Hyp aggregates can redissociate resulting in fluorescent monomeric and biological active form of this molecule (Falk and Meyer 1994;Lavie et al 1995;Huygens et al 2005;Kascakova et al 2005). Our group has published several articles about the properties of Hyp/LDL complexes (Kascakova et al 2005;Mukherjee et al 2008;Gbur et al 2009;Huntosova et al 2010;Buriankova et al 2011).…”
Section: Introductionmentioning
confidence: 99%